1968
DOI: 10.1084/jem.127.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Hemopoietic Colony Studies

Abstract: In heavily irradiated mice, bone marrow regeneration of either endogenous or exogenous origin was shown to occur in discrete foci comparable to the more intensively studied spleen colonies. The number of endogenous bone marrow colonies was inversely related to dose of whole body X-irradiation. Endogenous marrow colonies were found after higher doses of irradiation than were endogenous spleen colonies. Most of them were granulocytic in nature. Exogenous bone marrow colonies in lethally irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(46 citation statements)
references
References 7 publications
1
45
0
Order By: Relevance
“…Pluripotent stem cells are thought to have a capacity for self-renewal and differentiation into all hematopoietic lineages and to play an important role in the long-term reconstitution of hematopoiesis after bone marrow transplantation. Improvement of experimental methods, such as the murine spleen colony assay and hemopoietic cell culture, has provided useful models to clarify the kinetics of pluripotent stem cells; some of the early studies emphasized the importance of the microenvironment in the proliferation and differentiation of stem cells rather than circulating humoral factors [ 1,2]. Lord and Wright, and Tejero et al suggested that the proliferation rate of the colony forming units in spleen (CFU-S) in bone marrow cells was controlled by locally produced stimulatory and inhibitory factors [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Pluripotent stem cells are thought to have a capacity for self-renewal and differentiation into all hematopoietic lineages and to play an important role in the long-term reconstitution of hematopoiesis after bone marrow transplantation. Improvement of experimental methods, such as the murine spleen colony assay and hemopoietic cell culture, has provided useful models to clarify the kinetics of pluripotent stem cells; some of the early studies emphasized the importance of the microenvironment in the proliferation and differentiation of stem cells rather than circulating humoral factors [ 1,2]. Lord and Wright, and Tejero et al suggested that the proliferation rate of the colony forming units in spleen (CFU-S) in bone marrow cells was controlled by locally produced stimulatory and inhibitory factors [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The major themes of these theories are intrinsic vs. instructive. The instructive models, [17][18][19] postulate that the microenvironment educates HSC to change. The models of intrinsic regulation of HSC diversity can be subdivided into stochastic and deterministic theories.…”
Section: Heterogeneity In the Hsc Compartmentmentioning
confidence: 99%
“…lar contact that regulates in vivo and in vitro hematopoieThese results suggest that LEC-1, but not LEC-2, provide an sis. [8][9][10] In vivo, it has been shown that bone marrow (BM) appropriate hematopoietic microenvironment for supporting stroma determines the differentiation of hematopoietic the proliferation and differentiation of primitive hematopoicells. 8,9 In vitro, Dexter et al established a system of longetic cells.…”
Section: Lec-1 Supported the Maintenance And Differentiation Of He-mentioning
confidence: 99%
“…[8][9][10] In vivo, it has been shown that bone marrow (BM) appropriate hematopoietic microenvironment for supporting stroma determines the differentiation of hematopoietic the proliferation and differentiation of primitive hematopoicells. 8,9 In vitro, Dexter et al established a system of longetic cells. This could explain the anatomical restriction of term BM culture using BM stroma cells; the system was able hematopoietic cells for growing in LEC-1 domains during liver to support the differentiation and proliferation of hematopoiextramedullary hematopoiesis.…”
Section: Lec-1 Supported the Maintenance And Differentiation Of He-mentioning
confidence: 99%
See 1 more Smart Citation